Correspondence between the results of functional analyses and brief functional analyses. (17th November 2017) - Muething, Colin S.; Call, Nathan A.; Lomas Mevers, Joanna; Zangrillo, Amanda N.; Clark, Seth B.; Reavis, Andrea R.
ABSTRACT: Purpose: This study sought to examine the correspondence between brief functional analyses and more thorough functional analyses as described in the model of functional assessment proposed by Vollmer et al. 1 Methods: A panel of trained clinicians indicated the presence/absence of specific functions of problem behavior based on graphic results from brief functional analyses and functional analyses conducted with 19 participants. These conclusions were compared across assessments. Results: The functions identified by the panel based on results of brief functional analyses had low correspondence with those of the more thorough functional analysis conducted with the same participants. Conclusions: Although brief-functional analyses appear regularly in clinical practice and the literature, findings from this study suggest that results may differ from those of more thorough functional analyses. Additional study is necessary to determine the cause of discrepant results between these two methodologies.